Dynamic Topology Evolution and Multi-Objective Routing Optimization for Efficient VANET Communication - Hao Wang (IEEE Access)
This paper presents a dynamic topology evolution model and a multi-objective routing optimization algorithm tailored for Vehicular Ad Hoc Networks (VANETs) to address the challenges of efficient routing in highly dynamic topologies. The proposed algorithm utilizes a Dynamic Topology Evolution (DTE) model to evaluate routing stability by capturing continuous changes in network topology. By integrating a cooperative relay mechanism and a multi-objective relay node selection method, the algorithm significantly enhances data transmission success rates and reduces end-to-end latency. Furthermore, the implementation of Dijkstra’s algorithm enables efficient path selection with low computational complexity. Simulations using real urban traffic data demonstrate that the proposed algorithm outperforms existing protocols in terms of packet delivery rates and transmission delays, particularly in complex urban environments.